2020
DOI: 10.1177/1747021820969144
|View full text |Cite
|
Sign up to set email alerts
|

Phonological but not semantic influences on the speech-to-song illusion

Abstract: In the speech to song illusion a spoken phrase begins to sound as if it is being sung after several repetitions. Castro et al. (2018) used Node Structure Theory (NST; MacKay, 1987), a model of speech perception and production, to explain how the illusion occurs. Two experiments further test the mechanisms found in NST–priming, activation, and satiation–as an account of the speech to song illusion. In Experiment 1 words varying in the phonological clustering coefficient influenced how quickly a lexical node cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Similarly, Vitevitch, Ng, Hatley, & Castro (2020) report that words with a high phonological clustering coefficient (which measures the tendency for phonological neighbors of a word to also be neighbors of one another) are perceived as more song-like after repetition.…”
Section: Proposed Mechanisms Of the Speech-to-song Illusionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, Vitevitch, Ng, Hatley, & Castro (2020) report that words with a high phonological clustering coefficient (which measures the tendency for phonological neighbors of a word to also be neighbors of one another) are perceived as more song-like after repetition.…”
Section: Proposed Mechanisms Of the Speech-to-song Illusionmentioning
confidence: 95%
“…Supporting a role for lexical deactivation in the illusion, they find that words from denser phonological neighborhoods and words from an unfamiliar language are rated as more song-like after repetition. Similarly, Vitevitch et al (2021) report that words with a high phonological clustering coefficient (which measures the tendency for phonological neighbors of a word to also be neighbors of one another) are perceived as more song-like after repetition.…”
Section: Proposed Mechanisms Of the Speech-to-song Illusionmentioning
confidence: 95%
“…Examining the speechto-song illusion from the theoretical and methodological perspective of speech perception, spoken word recognition, and language processing may continue to provide novel insights into this unique auditory illusion. Indeed, the use of the language processing model, node structure theory (MacKay, 1987), to account for the speech-to-song illusion has already led to a number of important discoveries about this illusion (Castro et al, 2018;Mullin et al, 2021;Vitevitch et al, 2020). In the General Discussion, we compare the NST account of the speech-to-song illusion to other accounts of the speech-to-song illusion.…”
Section: Discussionmentioning
confidence: 95%
“…Recent findings from Castro et al (2018; see also Mullin et al, 2021;Vitevitch et al, 2020) indicate that the mechanisms in NST (MacKay, 1987;MacKay et al, 1993)-priming, activation, and satiation-may explain how speech can be perceived as being song-like after several presentations. In NST, nodes are used to represent phonemes, syllables, words, and other types of linguistic information.…”
mentioning
confidence: 99%
“…The results of a number of behavioral experiments using conventional psycholinguistic tasks in laboratory settings have shown that certain network structures at various scales of the phonological network influence the production, recognition, and learning of spoken words in English. For example, the experiments in [ 18 ] considered a micro-scale measure, the (local) clustering coefficient, and how it influenced spoken word recognition (see also [ 19 , 20 , 21 , 22 ]). At the macro-scale, experiments by [ 23 ] examined how the location of words in the giant component (i.e., the largest group of connected nodes in a network) or in “lexical islands” (i.e., smaller groups of words that are connected to each other, but not to words in the giant component) of the phonological network influenced spoken word recognition.…”
Section: Introductionmentioning
confidence: 99%